Cultural Acculturation Found in the Practice of Tradition Petik Laut - Jonorman, Khairunisha Amshalia; Widiastutik, Anis; Ukhrowiyah, Haqikoh; Salsabila, Alma (CV. Era Digital Nusantara, 2024)
Petik Laut practice, which is carried out in coastal areas of East Java, Indonesia, is an expression of appreciation and prayer for protection by fishing communities. This study investigates cultural acculturation that occurs in the Petik Laut tradition in Payangan Beach, Jember, with a focus on the integration of various cultural and religious aspects. This study uses qualitative approaches such as interviews and a literature analysis to explore the two-day event's diverse agenda, which combines Hindu, Islamic, and Javanese cultural activities. This study emphasizes the Petik Laut tradition's function in conserving cultural identity, promoting communal cohesion, and adapting ancestral history to current situations. The findings show the tradition's ability to integrate spiritual, cultural, and social values, demonstrating its long-standing significance in Indonesia's diverse cultural environment. The tradition of petik laut is carried out for two days where there is a combination of Islamic and Javanese traditions in the ritual. This research illustrates that in a culture there is acculturation in its practices.